Denmark : Financial Sector Assessment Program; Technical Note; Stress Testing. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note describes the stress testing exercises carried out for the Danish commercial banking system and the insurance sector. The tests were conducted as part of the Financial Sector Assessment Program for Denmark and were developed in collaboration with the Danish Financial Supervisory Agency (DFSA) and Danmarks Nationalbank (DNB). Two approaches-bottom-up and top-down-were employed in the analysis. Results of the stress test show that under changing macroeconomic conditions, credit risk could materialize, causing a substantial deterioration in banks' results.